The impact of the global financial and economic crisis convergence process in OECD countries - Marianna Greta; Krzysztof Lewandowski (Comparative Economic Research. Central and Eastern Europe, 2015)
This paper analyzes the issue of convergence in OECD countries and tries to assess the effect of financial crisis on the process of convergence. In other words it will consider whether the global financial crisis pulled the economies of the organization together or pushed them apart. It tries to show whether the present crisis has had a similar effect on the convergence process as the Great Depression had 80 years ago. It will analyze the most important macroeconomic data from the period 2007-2012 and use a simple econometric model to establish the relationships and, in conclusion, compare the similarities and differences between these two economic events.
Keywords: 330; economic crisis; economic growth; OECD; convergence